Angiotensin II and aldosterone activate retinal microglia. (February 2020) - Rana, Indrajeetsinh; Suphapimol, Varaporn; Jerome, Jack R.; Talia, Dean M.; Deliyanti, Devy; Wilkinson-Berka, Jennifer L.
Abstract: Microglial cells are important contributors to the neuroinflammation and blood vessel damage that occurs in ischemic retinopathies. We hypothesized that key effectors of the renin-angiotensin aldosterone system, angiotensin II (Ang II) and aldosterone, increase the density of microglia in the retina and stimulate their production of reactive oxygen species (ROS) as well as pro-angiogenic and pro-inflammatory factors. Two animal models were studied that featured up-regulation of Ang II or aldosterone and included transgenic Ren-2 rats which overexpress renin and Ang II in tissues including the retina, and Sprague Dawley rats with ischemic retinopathy and infused with aldosterone. Complementary studies were performed in primary cultures of retinal microglia from neonatal Sprague Dawley rats exposed to hypoxia (0.5% O2 ) and inhibitors of the angiotensin type 1 receptor (valsartan), the mineralocorticoid receptor (spironolactone) or aldosterone synthase (FAD286). In both in vivo models, the density of ionized calcium-binding adaptor protein-1 labelled microglia/macrophages was increased in retina compared to genetic or vehicle controls. In primary cultures of retinal microglia, hypoxia increased ROS (superoxide) levels as well as the expression of the NADPH oxidase (NOX) isoforms, NOX1, NOX2 and NOX4. The elevated levels of ROS as well as NOX2 and NOX4 were reduced by all of the treatments, and valsartan and FAD286 also reduced NOX1 mRNA levels. A protein cytokine array of retinal microglia revealed that valsartan, spironolactone and FAD286 reduced the hypoxia-induced increase in the potent pro-angiogenic and pro-inflammatory agent, vascular endothelial growth factor as well as the inflammatory factors, CCL5 and interferon γ. Valsartan also reduced the hypoxia-induced increase in IL-6 and TIMP-1 as well as the chemoattractants, CXCL2, CXCL3, CXCL5 and CXCL10. Spironolactone and FAD286 reduced the levels of CXCL2 and CXCL10, respectively. In conclusion, our findings that both Ang II and aldosterone influence the activation of retinal microglia implicates the renin-angiotensin aldosterone system in the pathogenesis of ischemic retinopathies. Highlights: Angiotensin II and aldosterone increased the density of microglia in the retina. Blockade of the angiotensin type 1 receptor and aldosterone reduced reactive oxygen species and the expression of NADPH oxidase (NOX) isoforms in retinal microglia exposed to hypoxia. Blockade of the angiotensin type 1 receptor and aldosterone reduced the protein levels of pro-angiogenic and pro-inflammatory factors produced by retinal microglia in response to hypoxia.